An Attempt to Understand Cyber Security Management Process - Nowduri, Srinivas (Archives of Business Research, 2018)
Modern businesses are still thriving to achieve to a security level opting for cybersecurity, in the form of a cybersecurity management process (CMP), is detail at three levels. The first level focuses on the architectural and components of this CMP. The second level details the comprehensive view, and finally presents systems and complexity view. This work also proposes a cybersecurity management model, along with some challenging issues.